2008
DOI: 10.1590/s1516-635x2008000100004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of egg pre-storage heating period and storage length on the digestive tract of newly-hatched broiler chicks

Abstract: An experiment was carried out to evaluate the effect of different heating times of settable eggs of Cobb 500® broiler breeders before submitting them to different storage periods on body weight, digestive tract organ weights, and intestinal mucosa morphology of newly-hatched chicks. Settable eggs were distributed in a completely randomized experimental design with a 3 x 3 factorial arrangement: pre-storage heating periods (0, 6, 12 hours at 36.92°C) and storage periods (4, 9, 14 days at 12.06°C). Body weight a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…However, especially layer or parent stock hatcheries sometimes need to prolong the storage duration ( Tona et al., 2003b , Fasenko, 2007 ), dependent on the supply of hatching eggs, hatchery capacity, and market demand for day-old chickens ( Fasenko, 2007 ). Egg storage beyond 7 D is associated with a longer incubation duration ( Yassin et al., 2009 ), lower hatchability ( Tona et al., 2004 , Silva et al., 2008 ), lower chicken quality at hatch ( Silva et al., 2008 , Yassin et al., 2009 ), lower subsequent growth performance, and a higher posthatch mortality ( Tona et al., 2004 ). Table 1 shows that broiler chickens originating from eggs that were stored beyond 7 D did not seem to differ in chicken weight or YFBM at hatch but had a 0.9-g smaller residual yolk weight at hatch than chickens originating from eggs stored for less than 7 D, which may be explained by a longer incubation duration.…”
Section: Factors Affecting Residual Yolk Weight At Hatchmentioning
confidence: 99%
See 1 more Smart Citation
“…However, especially layer or parent stock hatcheries sometimes need to prolong the storage duration ( Tona et al., 2003b , Fasenko, 2007 ), dependent on the supply of hatching eggs, hatchery capacity, and market demand for day-old chickens ( Fasenko, 2007 ). Egg storage beyond 7 D is associated with a longer incubation duration ( Yassin et al., 2009 ), lower hatchability ( Tona et al., 2004 , Silva et al., 2008 ), lower chicken quality at hatch ( Silva et al., 2008 , Yassin et al., 2009 ), lower subsequent growth performance, and a higher posthatch mortality ( Tona et al., 2004 ). Table 1 shows that broiler chickens originating from eggs that were stored beyond 7 D did not seem to differ in chicken weight or YFBM at hatch but had a 0.9-g smaller residual yolk weight at hatch than chickens originating from eggs stored for less than 7 D, which may be explained by a longer incubation duration.…”
Section: Factors Affecting Residual Yolk Weight At Hatchmentioning
confidence: 99%
“…(2010) found that chickens from eggs stored for 4 D compared with 14 D had a higher YFBM of 0.5 g at hatch, but a comparable residual yolk weight (5.8 vs. 6.1 g, for eggs stored for 4 or 14 D, respectively) at 12 h after emergence from the eggshell. Silva et al. (2008) (4, 9, or 14 D of storage) and Yalçin et al.…”
Section: Factors Affecting Residual Yolk Weight At Hatchmentioning
confidence: 99%